Complex evaluation of coagulation, fibrinolysis, and inflammatory cytokines in SARS-CoV-2 infected pregnant women: a prospective, case-control study - Bagoly, Zsuzsa; Tóth, Eszter Lilla; Orbán-Kálmándi, Rita; Lóczi, Linda; Deli, Tamás; Török, Olga; Kozma, Bence; Baráth, Sándor; Singh, Parvind; Hevessy, Zsuzsanna; Tóth, Judit; Katona, Éva; et al. (Frontiers in Immunology, 2025)
BackgroundGiven the physiological hemostasis changes during pregnancy, limited data exists on COVID-19-induced inflammatory response and hemostasis alterations in pregnant women.ObjectivesTo test a comprehensive set of hemostasis and inflammatory cytokines in pregnancies with/without COVID-19 and correlate results with maternal and perinatal outcomes.Patients/methodsIn this observational case-control study, 100 women with acute COVID-19 at 24-40 gestational weeks (COVID-19+ group), and 100 healthy, age- and gestational week-matched, SARS-CoV-2 negative pregnant women (32 with proven recovery of COVID-19) were enrolled. All women were outpatients with mild/no symptoms at admission. Detailed hemostasis (fibrinogen, FVIII, FXIII, VWF, plasminogen, α2-plasmin inhibitor, PAI-1, thrombin generation, clot lysis, D-dimer) and inflammatory cytokine/chemokine panels were performed. Clinical parameters of pregnancy, labor and postpartum period were registered.ResultsCOVID-19+ women exhibited significantly lower FVIII, FXIII, plasminogen, higher VWF levels, decreased peak thrombin and enhanced clot lysis vs. controls. Despite mild/no symptoms, significantly elevated cytokine levels, including IL-6, INF-γ, MCP-1, and IL-18 were observed in COVID-19+ pregnancies, associated with distinct hemostasis alterations. Admission IL-1β, and IL-33 were significantly lower, while IL-18 was significantly higher in cases when COVID-19 became more severe, along with significantly decreased FVIII, FXIII and plasminogen. In the COVID-19+ group, postpartum hemorrhage (PPH) developed in 4 cases, associated with significantly reduced plasminogen, α2-plasmin inhibitor, and increased IL-8, IL-17A, IL-23 levels.ConclusionIn third trimester mild/asymptomatic COVID-19+ pregnancies, marked inflammatory cytokine changes, hemostasis alterations and enhanced fibrinolysis were found. A potential link between inflammation and PPH in the context of COVID-19 warrants further research.